2019
DOI: 10.1002/ajb2.1293
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore resistance in congeneric and sympatric Nothofagus species is not related to leaf habit

Abstract: Premise Two fundamental hypotheses on herbivore resistance and leaf habit are the resource availability hypothesis (RAH) and the carbon–nutrient balance hypothesis (CNBH). The RAH predicts higher constitutive resistance by evergreens, and the CNBH predicts higher induced resistance by deciduous species. Although support for these hypotheses is mixed, they have rarely been examined in congeneric species. Methods We compared leaf constitutive and induced resistance (as leaf polyphenol and tannin concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In this study, evergreen species resulted in resource conservative species, being their leaves less palatable to herbivores due to low nutrient content and high proportion of support tissue (Chabot & Hicks, 1982). Similar findings were reported by Piper et al (2019), where N. betuloides (similar evergreen species) was less consumed than N. pumilio. In turn, deciduous species in this study are identified as a resource acquisitive species, since they have higher specific leaf area and higher nitrogen concentrations than evergreen species, as Diehl et al, (2008) measured.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, evergreen species resulted in resource conservative species, being their leaves less palatable to herbivores due to low nutrient content and high proportion of support tissue (Chabot & Hicks, 1982). Similar findings were reported by Piper et al (2019), where N. betuloides (similar evergreen species) was less consumed than N. pumilio. In turn, deciduous species in this study are identified as a resource acquisitive species, since they have higher specific leaf area and higher nitrogen concentrations than evergreen species, as Diehl et al, (2008) measured.…”
Section: Discussionsupporting
confidence: 82%
“…For example a defoliation experiment on juveniles of N. pumilio showed an extremely high regrowth capacity and survival; however, recurrent defoliations by the caterpillar could have different effects. In fact, the outbreaks of O. amphimone occur much more frequently in some stands than in others [75,76], and a previous study found that leaf resistance to O. amphimone was similar between trees from a stand without outbreak history and counterparts from a recurrently outbreak-affected stand [79]. However, it remains unknown if N. pumilio populations without outbreak history are as tolerant to defoliation as populations recurrently affected by outbreaks.…”
Section: Nsc and Herbivorymentioning
confidence: 99%
“…Carbohydrate reserves enable plants to uncouple growth from C assimilation throughout the year, allowing survival under seasonal stressful conditions. Instead, soluble sugars serve as important regulators of both physiological adjustment of plants to drought and freezing stress (Larcher and Thomaser‐Thin, ; Meletiou‐Christou et al., ; Lloret et al., ; Yamada and Osakabe, ) and pathogen or herbivore attack (Tauzin and Giardina, ; Piper et al., ). Nonstructural carbohydrates are involved in frost resistance (Palacio et al., ; Sperling et al., ) by protecting plants from intracellular desiccation (Sung et al., ).…”
mentioning
confidence: 99%